Default Costs and Repayment of Underwater Mortgages - Jan K. Brueckner; James N. Conklin; N. Edward Coulson; Moussa Diop (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper explores an overlooked phenomenon in mortgage markets: repayment of underwater mortgages. Since repayment in this case requires the borrower to use out-of-pocket funds along with the proceeds from the house sale to settle the loan, it may appear unattractive and even irrational. But if the borrower's negative equity is less than the cost of default, which includes credit impairment and possible guilt, repayment of an underwater mortgage is a wealth-maximizing strategy. The paper shows that such repayment indeed occurs, and that it is affected by the same factors commonly used in previous studies of default: the magnitude of home equity and the borrower's credit score, which captures default cost. An increase in either variable raises the likelihood that the underwater loan is terminated by repayment rather than by default. In addition, the paper also generates an estimate of the magnitude of default cost, showing that it rises with borrower credit worthiness, a finding that is new to the literature.
Keywords: G51; 330; default prepayment mortgages